CLINICAL EFFECTS OF ORTHODONTIC TREATMENT ON PERIODONTAL STATUS. REVIEW - Ioana Sioustis; Maria-Alexandra Martu; Ionut Luchian; Cornelia Teodorescu; Diana-Cristala Kapp; Alexandru Iovan; Silvia Martu (Romanian Dental Association for Education, 2019)
The purpose of this review is to describe the most frequently observed changes of the periodontium caused by orthodontic treatment, in order to facilitate the collaboration and communication of the specialists. This review also aims to explore the literature to select specific critical concepts and multidisciplinary connections and to highlight the importance of speciality cooperation. An electronic search of the database was performed using the PubMed database. Modifications of soft and hard periodontal tissues during orthodontic treatment and maintenance are discussed to provide a more comprehensive picture of the possible interactions between these two interrelated disciplines.